Pembinaan Kelompok Tani Wanita Nagari Subarang Air Kabupaten Lima Puluh Kota dalam Pengelolaan Kebun Kakao Rakyat - Noveri, Noveri; Fitri, Elva Rahmi; Fajri, Fajri; Erlinda, Rita; Situmorang, Helentina; Amir, Syafri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Cocoa is one of the many plantation crops cultivated by people in the Subarang Air. Previously, this commodity was quite a trend to be planted by the community. However, it seems that this commodity is not being managed more seriously, so that many smallholder cocoa plantations and plants are no longer producing optimally. Devotion is necessary to provide enlightenment and understanding to women farmer groups in Subarang Air through increasing the capacity of farming communities in managing smallholder plantations. This activity aims to increase the capacity of farmers so that they can increase their insight and knowledge and environmentally friendly agricultural systems for the community so that their land productivity remains high and can be used continuously without causing damage to the land. The methods used in this activity are training and practice. The results obtained from this activity are that farmers are able to participate in every activity carried out and are able to apply knowledge. Keywords: cocoa, Kelompok Tani Wanita, development